Long memory in US real output per capita - Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper analyses the long memory properties of quarterly real output per capita in the US (1948Q1 2008Q3) using non-parametric, semi-parametric and parametric techniques. The results vary substantially depending on the methodology employed. Evidence of mean reversion is obtained in a parametric context if the underlying disturbances are weakly autocorrelated. We also examine the possibility of a structural break in the data and the results indicate that there is a slight reduction in the degree of persistence after the break that is found to occur in the second quarter of 1978.
Keywords: C22; O40; 330; fractional integration; long memory; convergence; Volkswirtschaft; Gesamtwirtschaftliche Produktion; Sozialprodukt; Messung; USA